Seven years to seven figures : the fast-track plan to becoming a millionaire - Masterson, Michael (John Wiley & Sons, 2006)
In Seven Years to Seven Figures, self-made millionaire and renowned wealth coach Michael Masterson reveals the steps you can take to accumulate seven-figure wealth within seven years--or less. Seven Years to Seven Figures will give you the tools to increase your income, get the highest possible returns on investments, save wisely--and secure your financial future faster than you may have ever dreamed.